2020
DOI: 10.3390/jcm9051566
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Transfusion, not Hemoglobin Variability, Is Associated with 3-Month Outcomes in Acute Ischemic Stroke

Abstract: Objectives: This study aimed to investigate whether transfusions and hemoglobin variability affects the outcome of stroke after an acute ischemic stroke (AIS). Methods: We studied consecutive patients with AIS admitted in three tertiary hospitals who received red blood cell (RBC) transfusion (RBCT) during admission. Hemoglobin variability was assessed by minimum, maximum, range, median absolute deviation, and mean absolute change in hemoglobin level. Timing of RBCT was grouped into two categories: admission to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Additionally, a recent study confirmed that patients who were anemic at the time of an ischemic stroke had a high risk for recurrence and development of cardiovascular disease and cardiovascular death within a year [2]. Furthermore, it was reported that delayed treatment of anemia during hospitalization with ischemic stroke was associated with poor outcome at 3 months [6]. Therefore, anemia is a risk factor for developing ischemic stroke and increases the chance of recurrence and mortality risk.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, a recent study confirmed that patients who were anemic at the time of an ischemic stroke had a high risk for recurrence and development of cardiovascular disease and cardiovascular death within a year [2]. Furthermore, it was reported that delayed treatment of anemia during hospitalization with ischemic stroke was associated with poor outcome at 3 months [6]. Therefore, anemia is a risk factor for developing ischemic stroke and increases the chance of recurrence and mortality risk.…”
Section: Introductionmentioning
confidence: 92%
“…Anemia is a common disease in about 10% of people aged ≥65 years and its prevalence increase with age [1]. Ischemic stroke is frequently accompanied by anemia; previous studies have confirmed an average prevalence rate of 15-20% [2][3][4][5][6], and a maximum prevalence of 30% [7]. These prevalence rates of anemia are not significantly different from the 33% for diabetes or atrial fibrillation, which are known major risk factors for developing ischemic stroke [8,9].…”
Section: Introductionmentioning
confidence: 96%
“…common disease in about 10% of people age ≥ 65 years 7 its prevalence increase with age.19 Ischemic stroke is frequently accompanied by anaemia, previous studies have confirmed an average prevalence rate of 15-20%. [20][21][22][23][24] and a maximum prevalence of 30%. 25 IDA is the most typical type of anaemia, accounting for nearly half of all anaemia cases worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…148 Observational studies have likewise reported an inconsistent relationship between RBC transfusion and clinical outcomes, and this inconsistent finding may be, at least partially, attributable to differences in methodology. 33,129,149,150 The optimal transfusion trigger for AIS patients therefore remains unclear until more robust clinical data are available.…”
Section: Acute Ischemic Strokementioning
confidence: 99%